Environmental Factors’ Effect on Stress Reduction of Employees: A Case Study on Farhangian University Staff in Tehran - Payedar Ardakani, Pegah; Ghanbaran, Abdolhamid; Sharghi, Ali (Journal of History Culture and Art Research, 2017)
One of the most important issues the contemporary societies encounter is the job stress. There are various factors affecting it, but not enough researches have been done on the role that environmental factors play. This paper presents an experimental study with 100 participants on the influence of environmental factors on employees’ stress level. This method uses information derived from field observations and answers to questionnaires distributed to employees and officials who are in the top management of the central organization of Farhangian University, Tehran branch. The results demonstrate that color, window, lighting and brightness, landscape, communications and interactions, flexibility, thermal convenience, noise convenience, cleanness, physical activity, privacy and accessibility play an important role in the stress of employees, suggesting that the architectures and designers should consider the aforementioned factors so they can create dynamic and pleasant office environments devoid of any stress.